2006
DOI: 10.1121/1.2359704
|View full text |Cite
|
Sign up to set email alerts
|

Whistle variability in South Atlantic spinner dolphins from the Fernando de Noronha Archipelago off Brazil

Abstract: A series of quali-and quantitative analyses were conducted to evaluate the variability of spinner dolphin whistles from the Fernando de Noronha Archipelago off Brazil. Nine variables were extracted from each whistle contour, and the whistle contours shapes were classified into the seven categories described in Driscoll ͑1995͒. The analysis showed mean beginning and ending frequencies values of 10.78 and 12.74 kHz, respectively. On average, whistle duration was relatively short, with mean values around 0.495 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 27 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…Indeed, Gaspari et al (2015) have found that the genetic structure (Hoffmann et al, 2012). However, where acoustic communication is mediated by learning processes (as in cetaceans), and therefore by cultural transmission (Bain, 1986;Ford, 1991;Janik & Slater, 2000), populations that are geographically but not genetically distant may also manifest acoustic variability (Camargo, Rollo, Giampaoli, & Bellini, 2007;Rendell & Whitehead, 2005;Rossi-Santos & Podos, 2006). Regardless of the mechanism responsible for such variability whether geographic distance and isolation, genetic variability, and/ or cultural drift (Wilkins et al, 2012), our results provide evidence for variability in whistles between the two populations.…”
Section: Geographic Variabilitymentioning
confidence: 99%
“…Indeed, Gaspari et al (2015) have found that the genetic structure (Hoffmann et al, 2012). However, where acoustic communication is mediated by learning processes (as in cetaceans), and therefore by cultural transmission (Bain, 1986;Ford, 1991;Janik & Slater, 2000), populations that are geographically but not genetically distant may also manifest acoustic variability (Camargo, Rollo, Giampaoli, & Bellini, 2007;Rendell & Whitehead, 2005;Rossi-Santos & Podos, 2006). Regardless of the mechanism responsible for such variability whether geographic distance and isolation, genetic variability, and/ or cultural drift (Wilkins et al, 2012), our results provide evidence for variability in whistles between the two populations.…”
Section: Geographic Variabilitymentioning
confidence: 99%
“…There are no published sound recordings from Australia. Their sounds have instead been document from Hawaii [230,[256][257][258][259][260][261][262], the Eastern Tropical Pacific [151,152], the northwestern Atlantic [174], Brazil [263][264][265] and the western Indian Ocean off Madagascar [266].…”
Section: Stenella Longirostris-long-snouted Spinner Dolphinmentioning
confidence: 99%
“…Intra-specific variation in this type of vocalization has been assessed both at macro-(differences that occur over long distances and between populations that are geographically separated (KREBS & KROODSMA 1980)) and micro-geographic scales (variation between contiguous groups; KREBS & KROODSMA 1980), especially for Tursiops spp. (WANG et al 1995;JONES & SAYIGH 2002;CAMPBELL 2004;MORISAKA et al 2005aMORISAKA et al , 2005bBARON et al 2008;MAY-COLLADO & WARTZOK 2008;HAWKINS 2010;MAY-COLLADO 2010), Stenella frontalis (BARON et al 2008), Pseudorca crassidens, Grampus griseus, Globicephala macrorhynchus and Globicephala melas (RENDELL et al 1999), Sotalia guianensis (AZEVEDO & VAN SLUYS 2005;ROSSI-SANTOS & PODOS 2006), Stenella longirostris (BAZÚA- DURÁN & AU 2004;CAMARGO et al 2006) and Stenella coeruleoalba PAPALE et al 2013).…”
Section: Introductionmentioning
confidence: 99%